Inside-Outsider Research Positionality: Experience from Field Work Undertakings in Goderich - JACKSON, Emerson Abraham (Journal of Research in Educational Sciences; Vol 13 No 15 (2022): JRES, Volume XIII, Issue 15, Winter 2022DO - 10.14505/jres.v13.15.02, 2022)
This study was championed with the aim of exploring the role of an Inside-outsider researcher, and in particular with respect to the researcher's experience during a 2021 field study undertakings in Goderich, Freetown, Sierra Leone. The methodologies employed were based on “Focus Group interviews and Participant Observations” on adult participants within the age group of 18+ years. The study revealed intricacies surrounding (ethical) positionality as an Inside-outsider researcher, with consciousness focused on the need to be completely removed from emotional incidences given historical ties in the community. The study outcome finally acknowledged the relevance of negotiating cooperation in a bid to build transforming structures associated with the provision of government support to avail relevant assets for residents’ use in the community. These are considered critical in reducing risks posed to the community on account of voracious and destructive livelihood activities pursued by residents in meeting personal / family livelihood needs.